(untitled) - Swan, Michael (Oxford, 1995)
Michael Swan is a writer specializing in English language teaching and reference materials. His interests include pedagogic grammar, mother-tongue influence in second language acquisition, and the relationship between applied linguistic theory and classroom language-teaching practice, and he has published a number of articles on these topics.
Keywords: English language; Study and teaching,Foreign speakers